2012
DOI: 10.1371/journal.pntd.0001638
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serotype-Specific Dengue Virus Infection with Clinical Manifestations

Abstract: BackgroundDisease caused by the dengue virus (DENV) is a significant cause of morbidity throughout the world. Although prior research has focused on the association of specific DENV serotypes (DENV-1, DENV-2, DENV-3, and DENV-4) with the development of severe outcomes such as dengue hemorrhagic fever and dengue shock syndrome, relatively little work has correlated other clinical manifestations with a particular DENV serotype. The goal of this study was to estimate and compare the prevalence of non-hemorrhagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
79
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 26 publications
11
79
1
4
Order By: Relevance
“…28,29 Compared with the other DENV serotypes, we noted that individuals with DENV-4 infection were significantly less likely to have persistence of at least one symptom, independent of demographic factors, temporal factors, and prior DENV infection status. Although no longitudinal study has evaluated the association of symptom persistence with specific DENV serotype, many cross-sectional studies of acute DENV infection have assessed clinical features among the different DENV serotypes, including variations in acute severity and specific manifestations 16,30,31 ; our findings provide more evidence of the distinct clinical differences among DENV serotypes.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…28,29 Compared with the other DENV serotypes, we noted that individuals with DENV-4 infection were significantly less likely to have persistence of at least one symptom, independent of demographic factors, temporal factors, and prior DENV infection status. Although no longitudinal study has evaluated the association of symptom persistence with specific DENV serotype, many cross-sectional studies of acute DENV infection have assessed clinical features among the different DENV serotypes, including variations in acute severity and specific manifestations 16,30,31 ; our findings provide more evidence of the distinct clinical differences among DENV serotypes.…”
Section: Discussionmentioning
confidence: 69%
“…Cutaneous manifestations have been welldescribed in dengue disease. 3,16,21 Typical descriptions include a macular or morbilliform rash, which may be pruritic, often appearing at the time of defervescence, and lasting from 2 to 5 days. Given that 76.7% of study subjects still had fever at their acute visit, a significant portion may not have developed cutaneous symptoms until immediately after their initial presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] This issue confounds the ability to compare our results with those that used different case classifications or that were conducted in a pediatric setting. [12][13][14][15][16] Our study in adolescents and adults showed that, in this series, specific clinical aspects existed for each serotype. The DENV-4 infections most often had a milder clinical profile, regardless of the immune status and the year of observation.…”
Section: Discussionmentioning
confidence: 98%
“…Those infected with DENV 1 had an increased prevalence of rhinorrhea. People infected with DENV 4 had a higher prevalence of cutaneous and respiratory symptoms, and an increased prevalence of pharyngeal congestion [5].…”
Section: Comparison Of the Four Dengue Virus Serotypesmentioning
confidence: 99%